Intraductal papillary mucinous neoplasm of the pancreas (IPMN): clinico-pathological correlations and surgical indications - Baiocchi, Gian Luca (BioMed Central, 2010)
BACKGROUND: Intraductal papillary mucinous neoplasms (IPMNs) are increasingly recognized entities, whose management remains sometimes controversial, due to the high rate of benign lesions and on the other side to the good survival after resection of malignant ones. METHODS: Retrospective analysis of a prospectively collected Western series of IPMN. RESULTS: Forty cases of IPMN were analysed (1992-2007). Most patients were symptomatic (72.5%); cholangio-MRI had the best diagnostic accuracy both for the tumour nature (83.3%) and for the presence of malignancy (57.1%). ERCP was done in 8 cases (20%), and the results were poor. Thirteen patients were treated by pancreatic resection and 27 were maintained in follow-up. Total pancreatectomy was performed in 46% of the cases; in situ and invasive carcinoma were recognized in 15.4% and 38.4% of the cases, respectively. The mean follow-up was 42 months (range 12-72). One only patients with nodal metastases died 16 months after the operation for disease progression, while 91.6% of the operated patients are disease free. Out of the 27 not resected patients, 2 out of 4 presenting a lesion at high risk for malignancy died, while the remaining are in good conditions and disease free, with a mean follow-up of 31 months. CONCLUSION: Therapeutic indication for IPMNs is mainly based upon radiological evaluation of the risk of malignancy. While the main duct tumours should be resected, preserving whenever possible a portion of the gland, the secondary ducts tumours may be maintained under observation, in absence of radiological elements of suspicion such as size larger than 3 cm, or a wall greater than 3 mm or nodules or papillae in the context of the cyst.